Ekspansi Teknologi : Degradasi Kapabilitas Mahasiswa dalam Berinteraksi Sosial - Virna Muhdelifa Desembrianti; Sheila Agustina; Triyono; Vinda Olivia Hanna (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2023)
Nowadays, electronic devices have become a very important part of everyone's life. Gadgets in particular, not only make it easier for someone to gain access to information quickly, but gadgets are also used as communication tools, entertainment, and learning tools which make significant changes to the way people interact with the environment around them. Uncontrolled use of gadgets makes them waste a lot of time in front of the screen, this tends to have an impact on emotional intelligence. Sherry Turkle believes,